ANALISIS PENDAPATAN USAHATANI PADI SAWAH DENGAN SISTEM TABELA DI DESA ONGKA TRIMUSPASARI KECAMATAN ONGKA MALINO KABUPATEN PARIGI MOUTONG - Aristiawan, Aristiawan; Muis, Abdul; Howara, Dafina (AGROTEKBIS, 2018)
The aim of this research was to determine the income of wetland rice farmers under direct seeding system in Ongka Trimuspasari village, Ongka Malino sub district, Parigi Moutong regency.  This research was carried out from January until February 2017. A Simple Random technique was used for respondent determination and Slovin formula for determining the respondent number of 30 farmers. The average revenue of the farmer using the direct seeding system was IDR 35,253,333/2.04ha or IDR 17,281,045.75/ha with the average total cost of 16,806,469/2.04ha or IDR 8,238,465.24/ha and the average income of IDR 18,446,864/2.04ha orIDR 9,042,581/ha.